A 2D Titanium Carbide MXene Flexible Electrode for High‐Efficiency Light‐Emitting Diodes. Issue 23 (30th April 2020) - Ahn, Soyeong; Han, Tae‐Hee; Maleski, Kathleen; Song, Jinouk; Kim, Young‐Hoon; Park, Min‐Ho; Zhou, Huanyu; Yoo, Seunghyup; Gogotsi, Yury; Lee, Tae‐Woo
Abstract: Although several transparent conducting materials such as carbon nanotubes, graphene, and conducting polymers have been intensively explored as flexible electrodes in optoelectronic devices, their insufficient electrical conductivity, low work function, and complicated electrode fabrication processes have limited their practical use. Herein, a 2D titanium carbide (Ti3 C2 ) MXene film with transparent conducting electrode (TCE) properties, including high electrical conductivity (≈11 670 S cm −1 ) and high work function (≈5.1 eV), which are achieved by combining a simple solution processing with modulation of surface composition, is described. A chemical neutralization strategy of a conducting‐polymer hole‐injection layer is used to prevent detrimental surface oxidation and resulting degradation of the electrode film. Use of the MXene electrode in an organic light‐emitting diode leads to a current efficiency of ≈102.0 cd A −1 and an external quantum efficiency of ≈28.5% ph/el, which agree well with the theoretical maximum values from optical simulations. The results demonstrate the strong potential of MXene as a solution‐processable electrode in optoelectronic devices and provide a guideline for use of MXenes as TCEs in low‐cost flexible optoelectronic devices. Abstract : A solution‐processed transparent conducting electrode with desirable properties including high electrical conductivity (≈11 668 S cm −1 ) and work function (≈5.1 eV) is achieved by using a 2D titanium carbide (Ti3 C2 ) MXene thin film. Precise control of the surface chemical composition and a neutralized hole‐injection layer prevent detrimental surface/interface oxidation of the MXene and enable a high‐efficiency organic light‐emitting diode that uses the solution‐processed MXene electrode.